1992
DOI: 10.1088/0022-3727/25/12/018
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conduction of evaporated thin films for 1,1-bis-(4,4'-diethylaminophenyl)-4,4-diphenyl-1,3-butadiene

Abstract: The authors investigated the electrical conduction and electroluminescence in evaporated thin films for 1,1-bis-(4,4'-diethylaminophenyl)-4,4-diphenyl-1,3-butadiene (DEPB) which can be used as the carrier transport layer of electrography. Holes are the majority charge carriers for electrical conduction in DEPB thin films. The current in DEPB thin films below 1 MV cm-1 and at -160 degrees C is of Schottky type. Currents below 0.3 MV cm-1 and above -80 degrees C are attributable to the space-charge-limited curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…space-charge-free, J /µ-F characteristics, the corresponding conductance J /F was found to show a quasi-Poole-Frenkel-type field dependence (figure 4(a)). This is in agreement with observations by other authors for metal interfaces with a number of polymers in which conduction is by hopping, and has been interpreted as Richardson-Schottky emission into the polymers (Mori et al 1992, Kanemitsu and Imamura 1987, Reucroft and Ghosh 1974. However, Akuetey and Hirsch (1991) and Abkowitz et al (1995) have pointed out that the Richardson-Schottky theory is strictly applicable to emission into free, or quasi-free, space only and is not a proper description for emission into the localized states of the hopping manifold.…”
Section: Results and Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…space-charge-free, J /µ-F characteristics, the corresponding conductance J /F was found to show a quasi-Poole-Frenkel-type field dependence (figure 4(a)). This is in agreement with observations by other authors for metal interfaces with a number of polymers in which conduction is by hopping, and has been interpreted as Richardson-Schottky emission into the polymers (Mori et al 1992, Kanemitsu and Imamura 1987, Reucroft and Ghosh 1974. However, Akuetey and Hirsch (1991) and Abkowitz et al (1995) have pointed out that the Richardson-Schottky theory is strictly applicable to emission into free, or quasi-free, space only and is not a proper description for emission into the localized states of the hopping manifold.…”
Section: Results and Analysissupporting
confidence: 90%
“…These show that, after applying the electric field, the current gradually decays to a steady value which is strongly dependent on the metal workfunction. Mori et al (1992) made steady dark-current measurements in evaporated BD between an indium-tin oxide anode and cathodes of various metals. They concluded that in these, probably microcrystalline, samples there was evidence of bipolar conduction unlike the case in doped polymer layers containing BD.…”
Section: Introductionmentioning
confidence: 99%
“…The hole mobility is estimated to be 1.37x10 -9 m 2 /Vs from the experimental curve. Since the hole mobility of -NPD is estimated to be 10 -8 m 2 /Vs order by means of time-of-flight (TOF) method [30], it is 1-order higher than the hole mobility obtained from SCLC model. If we use the hole mobility obtained from TOF method, we must modify the equation 1and need use the following shallow trap SCLC model.…”
Section: Analysis Of Hole Currentmentioning
confidence: 96%